The effect of mixing parameters and surface treatment on the properties of cordierite filled porous epoxy - Siti Noorkhartina Ishak (School of Materials Engineering, 2016)
This research started with the development of porous epoxy through the extraction of latex using water and toluene as extraction medium and compared between non ultrasonic and with ultrasonic methods, respectively. Then, acetic acid and ammonia were used to adjust the pH of the latex with different phr content. Cordierite was synthesized from kaolin, talc, and alumina powder. The weight ratio of alumina: talc : kaolin used in this project were at 2 : 2 : 5. Lastly, the effect of surface treatment using silane coupling agent on the properties of porous epoxy was studied.